Meckel's Diverticulum causing Intussusception in a Newborn - Dillip Kumar Das; Pravat Kumar Majumdar; Suprabha Shukla (EL-Med-Pub, 2015)
A neonate presenting with intussusception probably caused by Meckel's diverticulum is reported here.